Process of Bacterial Cellulose Production from Tofu Wastewater Without Pretreatment Using Acetobacter xylinum - Margono, Margono; Isnaeni, Nur; Amelia, Vika; Shohih, Esa Nur (Jurnal Bahan Alam Terbarukan, 2023)
Bacterial cellulose (BC) is an alternative cellulose source that warrants more investigation due to its limited efficiency and high production costs. This research aims to investigate the generation of bacterial cellulose from tofu wastewater using Acetobacter xylinum without pretreatment. The experiment was run on two media: tofu wastewater with and without additional sugar. The fermentation was run in a dark cabinet using a static batch method in numerous fermenter trays, each with a working volume of 1000 mL. Each experiment used 900 mL of tofu wastewater medium plus an extra 100 mL inoculum (equal to 10% v/v), which was then cultured at room temperature and harvested on days 6, 12, 18, 24, and 30. The weight of nata de soya, BC, and residual sugar were all measured from the samples. The results of the experiments revealed that the best incubation time was 18 days. The fermentation employing tofu wastewater medium with added sugar yielded nata de soya of 227.3 g/L and BC of 32.2 g/L, while the medium without added sugar yielded 103.9 g/L and BC of 9.3 g/L. The medium with added sugar yielded higher BC productivity, 1.79 g/L.day, compared to 0.57 g/L.day in the medium without added sugar. On the other hand, the BC results per sugar consumption were 0.62 g BC/g sugar and 0.36 g BC/g sugar, respectively, for the medium with and without added sugar.